Reflections on aspects of executive behaviour in the early railway companies in Britain. Issue 4 (2nd September 2014) - Proctor, Tony
Abstract : Purpose: – The purpose of the article is to examine aspects of executive behaviour relating to social responsibility in the British railway companies from their beginnings in 1830 until 1860. It offers a fruitful contribution to the literature and the understanding of responsibility, noting specifically the impact of the overall business and social culture prevalent at the times. Design/methodology/approach: – Discussion of the railways touches on various stakeholders. It uses the four responsibilities of Corporate Social Responsibility (CSR) [economic, legal, ethical and discretionary (philanthropic)] as a framework against which to examine some of the actions taken in the railway companies. Reference is also made to the prevailing business culture of the times and how it may have impacted management practices of the times. The study considers real-world phenomena, where management is an applied field and where scholarship ties to the real-world phenomena practitioners face. Findings: – A lack of Government participation in setting up the railways resulted in a slow reaction in terms of providing legislation to regulate the development and running of the railways. This, in turn, meant firms having to rely sometimes on their own discretion regarding what they considered responsible actions. While economic and social benefits of railways were in evidence, there was some evidence of financial irregularities, and safety issues for passengers were prominent issues of the day. Moreover, a lack of an efficient public relations function hindered dealing with public concerns. Despite impressive engineering achievements, some mistakes were made which involved loss of life and substantial financial costs. Originality/value: – The combination of a historical approach and the use of the theoretical framework of the four responsibilities of CSR provide a novel view on aspects of entrepreneurial activity in a early industrialisation context. The case here also underlines the importance of understanding the context in which innovations, influential in and to society, are introduced.